Um algoritmo distribuído de eleição de líder para a internet das coisas móveis - SILVA NETO, Marcelino Mendes da (2018)
Internet of Things (IoT) can be defined as the interaction of technologies from different areas, such as: ubiquitous computing, protocols, communication technologies, and devices with embedded sensors and/or actuators, called smart objects. The interconnection of thousands of heterogeneous, addressable objects with network connectivity enables them to collect and share data, helping to improve people’s lives. In some cases, objects have memory and processing restrictions and connectivity to medium- and long-range networks, thus requiring a local gateway to collect, process and forward this information over the Internet to consumer applications. The M-Hub is a middleware that enables gathering, processing and distribution of data from a large number of smart objects. The M-Hub runs on mobile devices, turning them into IoT gateways. It represents an autonomous entity, able to detect a set of objects available in its neighborhood and monitoring them independently of other M-Hubs in proximity. Hence, the same set of objects is monitored by several M-Hubs, so leading to the wastage of resources of communication, processing, and energy. In this context, this thesis presents a leader election algorithm for MHub middleware to allow communication and negotiation between different mobile devices, determining the best IoMT gateway available in the environment for each object discovered opportunistically. This work also presents a case study, experiments related to the time of detection and recovery of failure of the node and, finally, the complexity of the proposed algorithm based on the message passing.